Studi pengaruh waktu dan suhu recovery limbah katalis nikel terpakai (spent catalyst) pasca proses hidrogenasi RBDPO dengan metode kalsinasi - Hardiko, Muhamad Hendri; Ridwan , Muhammad; Nuraliyah, Andi (Journal of Innovation Materials, Energy, and Sustainable Engineering, 2024)
Many palm oil processing industries use hydrogenation catalysts to optimize yields and produce quantities of catalyst residues containing metals harmful to the environment. Residue catalyst disposal also creates new problems for the industry because the category includes hazardous waste. Use of nickel catalyst at PT. Dua Kuda Indonesia in 2007 as much as 54 tons / year, 2014 as much as 108 tons / year and year 2018 as much as 216 tons / year. The price of nickel catalyst in Indonesia also has a fairly high value of about Rp. 120,000,000, - per ton. This study focused on the recovery of nickel catalyst activity by washing with etanol and activation catalyst wich calsinasi at temperatur 300°C, 400°C and 500°C. In the characterization stage, to see functional groups used Fourier Transform Infrared (FT-IR) instrument instrument, X-Ray Diffraction (XRD) crystallization test and structural test with Scanning Electron Microscope (SEM). The hydrogenated catalyst, tested quantity, quality of nickel catalyst with Iodine Value Test.